IMPACT OF HERBAL BASED DIETS ON PRODUCTION EFFICIENCY OF BROILER - SHAILESH BHUSHAN SRIVASTAVA,; RAM NIWAS,; D. P. SINGH,; BRIJPAL BISEN, (The Bioscan, 2013)
The experiment was conducted with the aim to find out the effect of Indigenous herbal drug and market herbal drug (Livkey) on the performance efficiency of broiler chicks. Ninty nine broiler chicks (VenCobb - 400 strains) were selected with all the birds bearing almost similar body weight were randomly divided into three group’s first one as a control (T1 ) and second and third were T2 and T3 as a treated group respectively. Each group having 33 broiler chicks with three replications (11 birds in each) were reared under deep litter system. Both the groups offered broiler starter (2-28days) and finisher (29-42days) diet except variation in supplementation of with 50mL market herbal drug (Livkey) per kg feed and Indigenous herbal drug (W:A:M in the ratio of 50:25:25 respectively) @ 2%/kg diet in T2 and T3 treated groups respectively. The results showed a significant difference in terms of body weight gain, feed consumption, feed conversion ratio (FCR), performance efficiency and dressing percentage in T3 group as compared to T2 group followed by T1 group. During the trial the mortality percentage were found to be minimum in T3 and T2 group followed by T1 group